2017
DOI: 10.1371/journal.pone.0176006
|View full text |Cite
|
Sign up to set email alerts
|

A bis-sulphamoylated estradiol derivative induces ROS-dependent cell cycle abnormalities and subsequent apoptosis

Abstract: Clinical trials have revealed that the potential anticancer agent, 2-methoxyestradiol (2ME2) has limitations due to its low bioavailability. Subsequently, 2ME2 derivatives including (8R,13S,14S,17S)-2-ethyl-13-methyl-7,8,9,11,12,13,14,15,16,17-decahydro-6H-cyclopenta[a]phenanthrane-3,17-diyl bis(sulphamate) (EMBS) have shown improved efficacies in inducing apoptosis. However, no conclusive data exist to explain the mode of action exerted by these drugs. This study investigated the mode of action used by EMBS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Due to previous studies that demonstrated that sulphamoylated compounds induce antiproliferative effects via ROS production [ 8 ], ROS scavengers were utilized to identify the different ROS involved in the antiproliferative activity exerted by sulphamoylated compounds such as ESE-one. Three out of six scavengers (tiron, trolox, DMTU) had a rescue effect in the antiproliferative action induced by ESE-one.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to previous studies that demonstrated that sulphamoylated compounds induce antiproliferative effects via ROS production [ 8 ], ROS scavengers were utilized to identify the different ROS involved in the antiproliferative activity exerted by sulphamoylated compounds such as ESE-one. Three out of six scavengers (tiron, trolox, DMTU) had a rescue effect in the antiproliferative action induced by ESE-one.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of N-acetyl cysteine (NAC) abrogated antiproliferative activity, cell cycle arrest and cell death suggesting that ROS production is essential for the ability of EMBS to induce cell death. However, the specific ROS-dependent signaling cascade induced by EMBS including the relevant ROS involved remains unknown [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have shown that sulfamoylated compounds such as 2-methoxyestradiol-bis-sulphamate and 2-ethyl-13-methyl-decahydro-6-cyclopenta[a]phenanthrane-3,17-diyl bis-sulfamate (EMBS) reduce cell growth and induce aberrant cell cycle activity in several tumorigenic cell lines including MCF-7 and MDA-MB-231 breast tumorigenic cell lines and the SNO esophageal tumorigenic cell line [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. In addition, the antiproliferative and antimitotic activity exerted by EMBS in breast cancer cell lines was abrogated by N-acetyl cysteine (potent scavenger of reactive oxygen species) indicating that these effects induced by EMBS are dependent on increased reactive oxygen species generated due to exposure to EMBS [ 8 ]. Further studies demonstrated that exposure to sulfamoylated compounds, including ESE-one, resulted in decreased cell growth and increased quantities of hydrogen peroxide and superoxide when compared to their counterparts that was not sulfamoylated which had no significant effect.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is the natural, regulated, destructive mechanism of the cell that disassembles unnecessary components. Various studies highlight that the therapeutic agents to treat cancer act by inhibiting cell cycle, apoptosis, and autophagy ( 4 , 5 ). These agents affect the cell cycle and cause autophagy through multi-signaling pathways within the cells.…”
Section: Introductionmentioning
confidence: 99%